The ACE2-Ang-(1‑7)-Mas Axis Modulates M1/M2 Macrophage Polarization to Relieve CLP-Induced Inflammation via TLR4-Mediated NF-кb and MAPK Pathways - Pan H (Dove Medical Press, 2021)
Hang Pan, Wenhan Huang, Zhongjie Wang, Feifeng Ren, Lei Luo, Jun Zhou, Mengxue Tian, Lin Tang Department of Rheumatology and Immunology, Second Affiliated Hospital of Chongqing Medical University, Chongqing, People’s Republic of ChinaCorrespondence: Lin TangDepartment of Rheumatology and Immunology, Second Affiliated Hospital of Chongqing Medical University, 76 Linjiang Road, Yuzhong District, Chongqing, People’s Republic of ChinaTel +86 13795683033Fax +86 23 62888265Email hopetang@163.comPurpose: Angiotensin 1– 7 [Ang-(1-7)] has been identified as an important anti-inflammatory and anti-fibrotic factor. This study determined how the ACE2-Ang-(1-7)-Mas axis affected M1/M2 macrophage polarization and thus contributed to anti-inflammatory processes in the cecal ligation and puncture (CLP)-induced inflammation model.Materials and Methods: ELISA, western blotting, and qRT-PCR were used to verify that Ang-(1-7) decreased the expression of pro-inflammatory cytokines and increased anti-inflammatory cytokines. The differentiation of M1/M2 macrophages was assessed by flow cytometry for assessing the cell-surface markers, CD86 and CD206. The related key receptors and pathways were analyzed by Western blotting, qRT-PCR, and immunofluorescence. CLP-induced inflammatory mice models were used for in vivo studies. Hematoxylin and eosin and immunohistochemical and immunofluorescence staining protocols were used to analyze histological changes in the spleen, and the related key pathway proteins were analyzed by western blotting.Results: Ang-(1-7) decreased the expressions of the TNF-α and IL-6 pro-inflammatory cytokines and increased the expressions of the IL-4 and IL-10 anti-inflammatory cytokines. INOS and TNF-α, which represented M1 macrophage polarization, were decreased by Ang-(1-7). ARG1 and CD163, which represented M2 macrophage polarization, were increased by Ang-(1-7). Both Mas receptor and ACE2 are expressed on macrophages. Furthermore, the ACE2-Ang-(1-7)-MAS axis modulated macrophage polarization by ameliorating TLR4 expression and regulating the NF-кB and MAPK pathways. In addition, splenomegaly and macrophage infiltration were observed in the spleen of the CLP-induced mouse models and macrophages in the spleen suspension of CLP models were shifted to M1 phenotype and were effectively inhibited by Ang-(1-7) via the TLR4-mediated NF-кB and MAPK pathways, which could be partially rescued by A-779.Conclusion: Ang-(1-7) inhibited inflammatory responses in vivo and in vitro, and repressed macrophage polarization toward the M1 phenotype and promoted it toward the M2 phenotype, which provided new evidence for the anti-inflammation activity of the ACE2-Ang-(1-7)-MAS axis.Keywords: ACE2-Ang-(1‑7)-MAS axis, macrophage polarization, sepsis, NF-kB pathway, MAPK pathway